The economic context of realizing socioeconomic rights in South Africa - Philippe Burger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The South African constitution is considered progressive and transformative in intention due to its inclusion of socioeconomic rights, such as the right to education, land, food, and healthcare. However, some of these rights are qualified by the availability of resources to the state, which places an imperative on the state to realize these rights progressively as resources become available. The deteriorating economy, low economic growth, and worsening public finances have led to increasing pressure on the government to cut its expenditure to regain fiscal sustainability and stem the growth of the government's debt burden. This threatens to roll back the progressive realization of socioeconomic rights, a phenomenon known as retrogression. A range of individuals and organizations oppose the cut-back of expenditure. The paper addresses how the government should reconcile the imperative placed on it by the constitution to realize socioeconomic rights with limited and shrinking resources available to do so.
Keywords: H5; K38; O23; O43; 330; socioeconomic rights; retrogression; economic growth